Forecasting time and place of earthquakes using a semi-Markov model: With case study in Tehran province - Ramin Sadeghian (Journal of Industrial Engineering International, 2012)
The paper examines the application of semi-Markov models to the phenomenon of earthquakes in Tehran province. Generally, earthquakes are not independent of each other, and time and place of earthquakes are related to previous earthquakes; moreover, the time between earthquakes affects the pattern of their occurrence; thus, this occurrence can be likened to semi-Markov models. In our work, we divided the province of Tehran into six regions and grouped the earthquakes regarding their magnitude into three classes. Using a semi-Markov model, it proceeds to predict the likelihood of the time and place of occurrence of earthquakes in the province.
Keywords: 650; semi-Markov model; earthquake occurrence; forecasting; transition matrix